Search for Nonwage Job Characteristics: A Test of the Reservation Wage Hypothesis - Blau, David M. (Journal of Labor Economics, 1991)
Previous structural models of job search behavior have been based upon the reservation wage property. This article provides estimates of a more general search model that nests models with the reservation wage property. The estimates lead to rejection of the reservation wage property. The model includes hours of work in the utility function, but other nonwage job characteristics can be included as well. An experiment based on the estimated parameters indicates that a significant proportion of job offers would be mistakenly predicted to be accepted or rejected under the restrictions implied by the reservation wage property.